Manuseio de carga : sintomas musculoesqueléticos e indicadores psicossociais em ambiente real e efeito da adaptação de caixas na redução de fatores de risco - Nogueira, Helen Cristina (2012)
With the rapid development of civil aviation in Brazil there was a large number of subjects involved in the aircraft maintenance work. Much of workers develop tasks involving manual material handling (MMH), which already have evidenced musculoskeletal risks. However, workers from the aircraft maintenance industry suffer huge pressure due the safety issues and the quality of the work that is performed. There were no studies in the literature that addressed the risk factors present in this sector. Thus, the aim of Study 1 was to evaluate the psychosocial indicators, as well as reports of musculoskeletal symptoms and disorders among workers iof the aircraft maintenance industry. One hundred and one employees were assessed using the Nordic Musculoskeletal Questionnaire, a standardized physical examination, the Job Content Questionnaire and the Utrecht Work Engagement Scale. The results indicate that the workers are exposed to good psychosocial conditions, which have neither prevented the emergence of musculoskeletal disorders, nor the self reported pain and functional disability, particularly associated with the lower back. As the MMH was the main activity performed by the aircraft maintenance workers assessed, musculoskeletal disorders seem to be associated with the biomechanical characteristics of this activity. Despite the risks already identified, the literature suggests some strategies for reducing the physical load imposed to the musculoskeletal system during MMH. These strategies such as the implementation of handles on boxes, ensuring better coupling object/hands during handling. However, the recommendations of adaptations in boxes are not conclusive regarding handle placement, and their impact on workers' musculoskeletal conditions. Thus, the Study 2 was conducted based on a systematic literature review. The aim was to synthesize evidence regarding the effect of adjustment on boxes, aiming at reduction of musculoskeletal load. A survey was conducted in the following databases: Embase, Pubmed / Medline, Web of Science, and Lilacs Bireme CINAHAL, Sportdiscuss, Cochrane. Two reviewers independently selected the relevant studies, and any disagreements were solved by consensus. Cross-sectional studies were included. The scale proposed by Ariens (2000) was used to assess the quality of the studies included in this review. The electronic search yielded a total of 1170 references published in English. At the end of the selection process, and after manual search of references, the selection included 15 cross-sectional studies. Due to do the great methodological variability, regarding both methods and the proposed adaptations (size and mass of boxes), associated with the low quality of the studies prevented the synthesis of evidence. There is a need of using objective and subjective methods to evaluate standardized boxes with handles, which can also be applied to the assessment of other ergonomic interventions. Furthermore, the handles should be investigated using various positions and inclinations, and the MMH has to be carried out to different heights, in order to provide more conclusive evidence to support the implementation of those adaptations in the occupational practice. Experienced subjects have also to be considered in future studies.